2020
DOI: 10.1038/s41409-020-01153-1
|View full text |Cite
|
Sign up to set email alerts
|

Midostaurin after allogeneic stem cell transplant in patients with FLT3-internal tandem duplication-positive acute myeloid leukemia

Abstract: We evaluated standard-of-care (SOC) treatment with or without midostaurin to prevent relapse following allogeneic hematopoietic stem cell transplant (alloHSCT) in patients with acute myeloid leukemia (AML) harboring internal tandem duplication (ITD) in FLT3. Adults (aged 18–70 years) who received alloHSCT in first complete remission, had achieved hematologic recovery, and were transfusion independent were randomized to receive SOC with or without midostaurin (50 mg twice daily) continuously in twelve 4-week cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 28 publications
1
84
0
Order By: Relevance
“…In the RADIUS trial, Maziarz et al randomized 60 FLT3-ITD + AML midostaurin versus standard of care (SOC). 62 This was an open label trial and midostaurin treatment was given for 12 months. The primary out- AML: acute myeloid leukemia; chemo: chemotherapy; CR: complete remission; CHR: complete hematologic remission; d: day; EFS: event-free survival; FLT3: fms like tyrosine kinase 3; HR: hazard ratio; ITD: internal tandem duplication; n: number; mido: midostaurin; OS: overall survival; RFS: relapse-free survival; SOC: standard of care; TKD: tyrosine kinase domain; TKI: tyrosine kinase inhibitor; y: years.…”
Section: Midostaurinmentioning
confidence: 99%
“…In the RADIUS trial, Maziarz et al randomized 60 FLT3-ITD + AML midostaurin versus standard of care (SOC). 62 This was an open label trial and midostaurin treatment was given for 12 months. The primary out- AML: acute myeloid leukemia; chemo: chemotherapy; CR: complete remission; CHR: complete hematologic remission; d: day; EFS: event-free survival; FLT3: fms like tyrosine kinase 3; HR: hazard ratio; ITD: internal tandem duplication; n: number; mido: midostaurin; OS: overall survival; RFS: relapse-free survival; SOC: standard of care; TKD: tyrosine kinase domain; TKI: tyrosine kinase inhibitor; y: years.…”
Section: Midostaurinmentioning
confidence: 99%
“…Given the broad kinome of sorafenib, which inhibits several non-FLT3 targets, future studies evaluating TKIs with more specificity for FLT3 would be of great interest to determine whether these clinically beneficial effects are due to on-target FLT3 inhibition or more broad inhibition of leukemic and immunologic kinase activity. Studies using other TKIs in the post-HSCT setting, including midostaurin, recently concluded (NCT04027309) [ 103 ], and a study including gilteritinib is underway (NCT02997202).…”
Section: Mrd-directed Therapeutic Approachesmentioning
confidence: 99%
“…Conversely, Midostaurin maintenance following alloHSCT has not proved to improve patient outcomes in the recent phase 2 open-label randomized RADIUS trial of the standard of care (SOC) with or without Midostaurin after alloHSCT for FLT3-mutated AML patients [ 48 ]. In this trial, 60 adults (aged 18–70 years old) patients who received alloHSCT in first complete remission, were randomized to receive standard of care with or without Midostaurin (50 mg twice daily) continuously in 12 four-week cycles.…”
Section: Pharmacological Inhibition Of Flt3 In Amlmentioning
confidence: 99%